Subsistence hunting impacts wildlife assemblages and functional ecology in tropical forests - Bradley Cain; Julia E. Fa; Rajan Amin; Jacqueline Morrison; Eva Avila Martin; Stephan M. Funk; Martin Jones; David P. Mallon; Robert Okale; Guillermo Ros Brull; Selvino R. de Kort (Scientific Reports)
Abstract Unsustainable wild meat hunting poses a significant threat to wildlife and tropical forest ecosystems. While high levels of extraction linked to commercial trade have received significant attention, the sustainability of subsistence hunting by Indigenous Peoples in Africa has been less studied. Understanding how changing lifestyles, particularly the sedentarisation of former hunter-gatherers, have affected the use of forest resources is crucial for wildlife conservation and livelihoods. The spatial management of hunting through the establishment of no-take zones, which act as sources for adjacent hunting areas, offers promise for the sustainability of Indigenous livelihoods. We conducted an extensive camera trap study in hunting areas subject to source-sink dynamics used by 10 sedentarised Baka communities. We compared species richness, occupancy, abundance, and community composition to a relatively non-hunted reference area in the adjacent Dja Faunal Reserve. Subsistence hunting by the Baka had a limited impact on species richness but significantly altered community composition and the abundance of carnivores, seed dispersers and granivores. These changes highlight that even the spatial management of hunting may have consequences for the sustainability of hunting systems and the functional ecology of tropical forests.